A Reinterpretation of Evidence for the Endothelial Glycocalyx Filtration Structure - Arkill, Kenton P. (Frontiers in Cell and Developmental Biology, 2021)
The endothelial glycocalyx is thought to be the primary macromolecular filter for fluid flux out of the vasculature. This filter maintains the higher protein concentration within the vessel lumen relative to the tissue. Whilst the arguments for the endothelial glycocalyx being the size filter are convincing the structural evidence has been limited to specialized stains of perfusion fixed tissue, which are further processed for resin embedding for transmission electron microscopy. The staining and processing of the delicate pore structure has left many researchers struggling to interpret the observed surface coat. Previous work has alluded to a 19.5nm spacing between fibers; however, whilst repeatable it does not give an endothelial glycocalyx pore size consistent with known glycosaminoglycan molecular structure due to the required fiber thickness of >10nm. Here a new interpretation is proposed based on the likelihood that the electron micrographs of are often of collapsed endothelial glycocalyx. The 19.5nm spacing measured may therefore be the core protein of the proteoglycans with the glycosaminoglycans wrapped up around them rather than in an expanded in-vivo state. The concept is explored to determine that this is indeed consistent with experimental measurements of permeability if the syndecans are predominately dimerized. Further an alteration of core protein lattice from hexagonal packing to square packing dramatically changes the permeability which could be facilitated via known mechanisms such as transient actin binding.